EFFORTS TO IMPROVE STUDENT LEARNING OUTCOMES USING THE TIME TOKEN STRATEGY IN THE LEARNING OF CIVILITY EDUCATION - Mardhiah, Ainol (BRIGHT VISION Journal of Language and Education, 2022)
This study aims to analyze efforts to improve student learning outcomes using the time token strategy in Civics learning at MIS Cot Keutapang. This study used a class action research approach (PTK) for 2 cycles. The results of the study can be concluded that the use of the time token method can improve the learning outcomes of Civics students on Heroism and Patriotism in class IV students of MIS Cot Keutapang. Based on the results of the implementation of learning corrective actions, it can be stated that in the pre-cycle only 8 students (28.57%) achieved the KKM target of 70. After implementing the first cycle actions there were 18 students (64.29%) who had reached the KKM target. and in the evaluation results of cycle II there were 28 students (100.00%) students who had achieved learning mastery.